HUBUNGAN KARAKTERISTIK DAN UPAYA RESILIENSI DENGAN TOXIC RELATIONSHIP YANG TERJADI SAAT BERPACARAN PADA MASA REMAJA - Novita*, Regina Vidya Trias; Christianty, Vierni Augusta; Yusandra, Evra (Jurnal Penelitian Keperawatan Medik, 2023)
Based on data from Catatan Tahunan (CATAHU) of the National Commission on Violence Against Women in 2019, there were 2,073 cases of dating violence. Victims of dating violence mostly occur in adolescents aged 13 - 17 years with 63 cases, and at the age of 18 - 24 years with 17 cases. According to the counseling teacher, adolescents at SMK Mitra Bakti Husada find it difficult to concentrate during the learning process, lack of motivation in learning, cannot do the assigned tasks well, and academic grades are declining. The purpose of this study was to analyze the relationship between characteristics and resilience efforts with toxic relationships that occur when dating during adolescence at SMK Mitra Bakti Husada. This research design uses quantitative, descriptive, and correlation research with a cross sectional approach. The total number of respondents was 155 with adolescent research respondents. This study used non-probability sampling method with purposive sampling technique. The results showed that there was a correlation between age (0.000); gender (0.000); length of dating (0.000) and resilience efforts (0.016) with toxic relationships. It is hoped that the results of this study can be used as feedback for schools to provide counselling on resilience efforts and toxic relationships, so that the students can avoid toxic relationships and overcome conflicts that occur in dating relationships by establishing better communication relationships so that problems can be resolved appropriately without the use of violence.